EDITOR'S PREFACE - Lisdiyanti, Puspita (Annales Bogorienses, 2004)
The editors would like to announce that, in the year of 2002 and 2003, The Research Centre for Biotechnology, The Indonesian Institute of Sciences (LIPI) did not publish Annales Bogorien es New Series due to some management problems. The last issue was published with Volume 8, Number 2, 2001. Under new editors, in this year of 2004, continuing the previous volume thi journal is published again starting with Volume 9, Number 1. In this ninth edition of Annales Bogorienses, we would also like to introduce a new I ok of this journal to our readers. We will continue to publish this journal periodically twice a year (in June and December).Many thank to all the author for their efforts, attention and time throughout the editing process that make this current edition become possible. Tolerance of our editorial judgment is mu h appreciated. We encourage our readers to submit original papers on topics of interest to life sciences researcher . December, 2004M. Ahkam Subroto Chief Editor